2021
DOI: 10.5204/ssj.1784
|View full text |Cite
|
Sign up to set email alerts
|

Digital Disruption in the COVID-19 Era: The Impact on Learning and Students’ Ability to Cope with Study in an Unknown World

Abstract: The COVID-19 pandemic will forever be known as a disruptive dilemma that impacted many industries in Australia.  For the university sector, sudden lockdown and social distancing rules resulted in an acceleration in the provision of learning and teaching via online platforms, creating new challenges for students and educators. This project explored the ways in which an enabling course supported students through the forced transition from face-to-face classes to online learning due to the COVID-19 restrictions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Students in on-campus enabling, or university pathways programs, also had to make the transition to online study once Covid-19 arrived. Research into their experiences (James et al, 2021) found that they too mostly "adapted and enjoyed the flexibility and convenience of studying at home" (p. 10). This was indicated by comments such as: "It was so much easier not having to drive to campus for classes and to be able to do many things around class time" and "being able to attend lectures anywhere" (p. 8).…”
Section: Online Learning Literature -2020 and Beyondmentioning
confidence: 99%
“…Students in on-campus enabling, or university pathways programs, also had to make the transition to online study once Covid-19 arrived. Research into their experiences (James et al, 2021) found that they too mostly "adapted and enjoyed the flexibility and convenience of studying at home" (p. 10). This was indicated by comments such as: "It was so much easier not having to drive to campus for classes and to be able to do many things around class time" and "being able to attend lectures anywhere" (p. 8).…”
Section: Online Learning Literature -2020 and Beyondmentioning
confidence: 99%
“…Currently, the majority of regional, online students are mature-aged (Crawford & Emery, 2021;Pollard, 2017) with online study being overwhelmingly chosen for the flexibility needed to combine family and work responsibilities with their studies (Hewson, 2018;Stone et al, 2019). Interestingly though, with COVID-19 restrictions having forced so many more students online during 2020-2022, recent research is showing how the flexibility of online learning is being similarly valued by the wider student cohort, with younger students also appreciating the flexibility to choose when, where and how they study (James et al, 2021;Martin, 2020;Savage, 2021). The research on which this paper is based (King et al, 2022) argued that RUCs have the potential to further increase the viability of online study for regional school-leaver students, with implications for both their post-school intentions and HE persistence.…”
Section: Introductionmentioning
confidence: 99%